PROFESIONALISME APARATUR DALAM PENYALURAN BERAS SEJAHTERA DI KELURAHAN MALALAYANG SATU TIMUR - Mabala, Julita Fitria; Rorong, Arie Junus; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : This study aims to determine how Professionalism of the apparatus in the distribution of prosperous rice in the eastern malalayang village. This research was conducted in may 2017. This research used qualitative method that is research type used to research on natural object condition where the researcher is a key instrument, data collection technique is done by tringulation (merges), data analalysis in inductive and the results of research qualitative emphasizes the meaning of gener-lation. Infomants in this study amounted to 12 people, namely head of urban village 1 person, head of environment 3 people, implementing unit of distribution and citizen counted 7 people. The results of this study note that the pofessionalism of the apparatus in the distribution of prosperous rice in the eastern malalayang village seen from the aspect of creative, innovation and responsiveness is good enough, but if measured in terms of ablitity can not be said professional. Based on existing research in view of the accuracy of the administration has not been met well, still found data collection that has not been right target due to lack of coordination and cooperation between urban village apologists. Referring to some of the results of this study, then as a suggetion and solution and problem solving in this research are: (1). The goverment should be more critical in responding to any good public complaints between the village government on beneficiary households (3). Every year needs to be done data collection again because poverty it self is relative meaning in the moon alone can move from poverty to prosper or vice versa (4). The availability of a box complaints or suggestions in each village, because considering there are people who may be embarrased or afraid to submit complaints and suggestions. (5) the importance of socialization between the community and the village apparatus regarding the distribution of propperous rice.Key word: Pofessionalism, Apparatus